CP-Based SBHT-RLS Algorithms for Tracking Channel Estimates in Multicarrier Modulation Systems - H. Ali (Journal of Electrical and Computer Engineering)
Cyclic prefix (CP) in multicarrier modulation systems has been considered as an alternative to the training sequences to track channel estimates. In this paper, two new algorithms are developed that exploit CP from their data detection part and employ systolic block Householder transformation recursive least squares (SBHT-RLS) algorithms for channel tracking in multicarrier systems. The new methods are compared with the existing CP exploiting correlation matrix based block RLS (CMB-RLS) channel tracking approach to outline their relative advantages. Aspects of computational complexity and parallel implementation are addressed, and the algorithms are tested in terms of their channel estimation and tracking capabilities. Performance of the algorithms is also evaluated for varying forgetting factor parameter values, constellation size, and word lengths. Floating-point and fixed-point simulations are tailored to illustrate pertinent tradeoffs.